Westonci.ca connects you with experts who provide insightful answers to your questions. Join us today and start learning! Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
Answer:
(2, 6)
Step-by-step explanation:
if you meant for both of the y to be the same then this should be right
Answer:
(2,6)
Step-by-step explanation:
*this is actually elimination*
1st- Turn both of them into standard form.
y=9x-12 ---> 9x-y=12
y=3x --> 3x-y=0
--
Multiply 9x-y=12 by -1
-9x+y=-12
3x-y=0
-6x=-12
divide by 6
x=2
--
Plug 2 into the first equation
9(2)-y=12
18-y=12
Cancel out 18 by subtracting -18 to both sides
-y=-6
divide by -1
y= 6
Answer: (2,6)
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.